Systematic Transcriptome Analysis Reveals the Inhibitory Function of Cinnamaldehyde in Non-Small Cell Lung Cancer - Chen, Ru; Wu, Juan; Lu, Chang; Yan, Ting; Qian, Yu; Shen, Huiqing; Zhao, Yujing; Wang, Jianzhen; Kong, Pengzhou; Zhang, Xinri (Frontiers in Pharmacology, 2021)
Cinnamaldehyde (CA) is the main component extracted from the traditional Chinese medicine cinnamon. Recent studies revealed that CA has antiviral and anti-tumor effects. However, the effect and mechanism of CA on non-small cell lung cancer (NSCLC) through whole transcriptome sequencing integrated analysis have not been systematically investigated. In this study, whole transcriptome sequencing was used to identify differentially expressed messenger RNAs (mRNAs), micro RNAs (miRNAs), and long non-coding RNAs (lncRNAs) that were influenced by CA and screen regulatory pathways. The results showed that CA significantly inhibited proliferation, invasion, and migration, whereas it induced the apoptosis of NSCLC cells. CA inhibited tumor growth in vivo. Gene ontology and Kyoto Encyclopedia of Genes and Genomes analysis revealed that these differentially expressed mRNAs were potentially implicated in the CA-suppressing malignant phenotypes of NSCLC. According to the competing endogenous RNA (ceRNA) hypothesis, a ceRNA network was constructed, including 13 mRNAs, 6 miRNAs, and 11 lncRNAs. Kyoto Encyclopedia of Genes and Genomes analysis of the 13 mRNAs in the ceRNA network showed that suppressors of cytokine signaling 1 (SOCS1), BTG anti-proliferation factor 2 (BTG2), and Bruton tyrosine kinase (BTK) were significantly enriched in the JAK/STAT signaling pathway, RNA degradation, and nuclear factor-κB (NF-κB) signaling pathway related to cancer. These findings indicated that SOCS1, BTG2, and BTK play an essential role in CA against NSCLC. Meanwhile, based on the ceRNA network, three lncRNAs (long intergenic non-protein coding RNA 1504 [LINC01504], LINC01783, and THUMPD3 antisense RNA 1 [THUMPD3-AS1]) and three miRNAs (has-miR-155-5p, has-miR-7-5p, and has-miR-425-5p) associated with SOCS1, BTG2, and BTK may be important in CA against NSCLC. Taken together, the present study demonstrated the activity of CA against lung cancer and its potential use as a therapeutic agent.